Reproducing Binary Sex: The Post-pandemic Theories from a Gender and Normative Perspective - Liotzis, Vangelis (Wydział Filozoficzny UAM, 2025)
During the notorious collective experience of COVID-19 pandemic, the prospect of a better future was featured in public interventions in the light of the recent painful circumstance. The theories of the post-pandemic world were prominent in this debate. This article attempts to examine some of them in order to investigate how broader social theories integrate the gender perspective. From the approximately forty English-language monographs by important scholars and thinkers which have characterised the relevant body of work, only ten of them have been found to contain explicit gendered references. Those were the selected sample of an analysis which was conducted from a social constructionist point of view articulated with a (neuro)feminist perspective. Despite the epistemological and methodological advances in the study of gender relations, the long dominant approach of binary sex constituted the basic framework of the analyses in the examined post-pandemic theories. This is a choice that does not advance the public debate on gender relations, since it de facto ignores and silences the multiplicity of gender identities and intersectional premises.
Keywords: COVID-19 pandemic; post-pandemic; binary sex; gender duality normative perspective